Study of biological characteristics of Pseudomonas aeruginosa strains isolated from patients with cystic fibrosis and from patients with extra-pulmonary infections - Stehling,Eliana Guedes (2008)
A total of 120 strains of Pseudomonas aeruginosa, isolated from cystic fibrosis (CF) patients (n = 80) and from patients having extra-pulmonary infections (n = 40) were studied regarding the presence of some virulence factors (hemolysin, gelatinase and elastase production) and presence of the algD and algU genes as detected by polymerase chain reaction-PCR. There was not a significant difference for the production of gelatinase and hemolysin between non-mucoid strains from CF patients and other isolates from extra-pulmonary infections and mucoid strains. The production of elastase was found to be significant among these strains. The algD gene was detected by PCR in all studied strains but the algU gene was detected only in 25% of the mucoid strains. Conclusion withdrawn from the results were: (i) hemolysin and gelatinase production although present in many strains of P aeruginosa should not be considered as general virulence factors for the mucoid phenotype but could help in the pathogenic process; (ii) elastase production could be a necessary virulence factor for the initial pathogenesis process; (iii) mucoid and non-mucoid phenotypes could also be expressed according to the host's tissues or environment, and finally, (iv) more than one regulator system for alginate production is probably present in each strain.